10 farmers’ organizations and public institutions in LAM empowered with tools to identify CSA options in line with seasonal forecasts - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
10 farmer organizations in 6 counties in LAM now have fully dedicated agro-climatic prediction and climate-site-specific agronomy analysis teams, sustainably producing climate-site-specific agronomic recommendations and seasonal agro-climatic forecasts in connection with national meteorological services. Two farmer organizations in Colombia adopted novel agro-climatic prediction practices; two national meteorological services strengthen their seasonal prediction capacity by automating the Climate Predictability Tool (CPT); 6 organizations use climate-site-specific agronomy to identify best CSA options.